THE INFLUENCE OF INTRINSIC FACTORS, EXTRINSIC FACTORS, CUSTOMER ATTITUDES AND CUSTOMER EXPECTATIONS TOWARD INTENTION TO STAY AT BUDGET HOTEL - Aslinda Mohd Shahril; Nur Nazirah Jusoh; Qi Xinzheng; Kandappan Balasubramanian, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study investigates the multifaceted influences shaping customer intention to stay at budget hotels, considering a comprehensive framework that encompasses intrinsic and extrinsic factors, as well as customer attitudes and expectations. As the budget hotel sector continues to grow in Malaysia, understanding the drivers behind customer decisions to stay in these establishments becomes crucial for both practitioners and researchers. The intrinsic factors measure service quality, safety and security that prompt customers to opt for budget accommodation. Extrinsic factors encompass external influences such as economic consideration such as price and rates that related aspects that impact customers' decisions. Customer attitudes, reflecting their overall perception and feelings towards budget hotels, are examined for their role in shaping intention to stay. Furthermore, this study delves into customer expectations, investigating how anticipated service quality, affordability, and other factors contribute to the decision-making process. By adopting a holistic approach, the research aims to provide valuable insights into the interplay between these factors and their collective impact on the intention to stay at budget hotels. A structure questionnaire was utilised to collect the data using quantitative method with 165 respondents. The online questionnaire was utilised for this survey and the instrument was evaluated using a five-point Likert scale on a questionnaire. Data for this study was obtained via a questionnaire and data was accessible using SPSS for the interpretation of independent and dependent variables. The finding showed four independent variables (intrinsic, extrinsic, attitude and customer expectation) positively correlated with dependent variable. The hypotheses are tested using reliability and correlation.